ANALISIS PENERAPAN ARSITEKTUR BIOMORFIK PADA PERANCANGAN MINAWISATA BERBASIS KULINER LAUT DI KOTA MAKASSAR - Ambo Dalle, Andi Patiroi Rasyid; Rahayu, Irma; Syuaib, Mayyadah (TIMPALAJA : Architecture Student Journals, 2026)
Makassar City has significant potential for developing the fisheries and coastal tourism sectors, supported by its strategic geographic location, abundant seafood resources, and culinary activities that serve as tourist attractions. However, the development of culinary-based minawisata facilities still needs to be properly organized to accommodate economic, recreational, educational, and environmental management activities sustainably. This study aims to design a culinary-based minawisata area in Makassar City using a biomorphic architectural approach as a design strategy that adapts the forms, patterns, and natural systems of marine organisms. The method used is a descriptive, qualitative approach with an architectural design focus, conducted through literature studies, precedent studies, site surveys, field observations, and analyses of function, site, form, circulation, and the application of biomorphic concepts. The design results show that the biomorphic approach is applied through building form transformations inspired by seashells, waves, coral reefs, and other marine organisms. In addition, the biomorphic concept is implemented in organic site planning, flowing circulation patterns, and a wastewater recycling system that mimics the filtering mechanisms of marine organisms. This design is expected to create a culinary minawisata area that is aesthetic, functional, environmentally friendly, and capable of supporting the economic and coastal tourism development of Makassar City..